Onteniente Hospital: surgeons & nurses (memorandum) - C. H.
041-0026-001 Miss MacDonald April 20, 1937 Onteniente Hospital - Surgeons & Nurses Mr. Gillies cannot do anything through the Socialist Medical Association which cannot be done by Dr. Morgan, and it would be wrong to cut across what he is doing. The Belgian rates are very much below British rates What Dr. Morgan says is probably true, - that it would be impossible to find a British doctor at £4 a week. C.H. 292/946/41/26